STRATEGIC COMPETENCY MAPPING AND ITS ROLE IN ENHANCING OUTPUT MANAGEMENT IN NAGPUR’S SMALL MANUFACTURING SECTOR - Siddiqui, Aftab Ali; Waiker, Vinod (International Journal of Research -GRANTHAALAYAH, 2025)
Strategic personnel management methods are essential for small-scale manufacturing firms to be competitive in this era of fast industrial transition. This research takes a close look at how strategic competence mapping has helped small-scale manufacturers in Nagpur with their output management. Competency mapping is the focus of this study because of its potential to boost productivity by revealing skill shortages and allowing for more efficient use of the workforce. Data is gathered from industry experts via interviews and structured surveys using a mixed-method approach. Key skills that impact performance are analysed. Higher efficiency, fewer operational bottlenecks, and better output quality are the results of a competence mapping framework that is well-structured, highlighting the need of connecting staff talents with organisational objectives. Additionally, the research offers practical suggestions for long-term development and addresses difficulties encountered by small-scale businesses when attempting to use competence frameworks. This study makes a significant contribution to the fields of industrial efficiency and human resource management by providing useful information for manufacturing sector executives, legislators, and HR professionals.